Wearable Sensors Based Remote Patient Monitoring using IoT and Data Analytics - Arora, Jatin (2019)
Quality of life is reducing due to numerous reasons such as poor eating habits, tobacco consumption, sedentary lifestyle and stress which all taken together to leadto several and sometimes serious health problems. The scenario becomes worse in rural areas due to the limited availability of clinical facilities. Here, peoplehave to visit hospitals, specialist doctors in citiesfor proper treatment and this results in wasteof time, money and resources. To mitigate such problems, wearable sensors based remote patient monitoring system using IoT and data analytics has been proposed. The proposed system is specifically aimed for cardiovascular diseases and canbe used to monitor the health condition of apatient even when heis at home, on the farmor any other place. The system also incorporates data analytics for the monitoring ofthe historical and current status of the patient’s health. The system is implemented using low-cost and compact componentssuch as Arduino Nano, ESP8266, MAX30100, DSB1820 etc.